Penerapan Metode Drill Dalam Pembelajaran Tari Sigeh Pengunten di SD N 3 Poncowati - Aline Rizky Oktaviari Satrianingsih; Endang Karana Pertiwi (Universitas Sarjanawiyata Tamansiswa, 2023)
This study uses the drill method to discuss the learning process of the Sigeh Pengunten Dance at SD N 3 Poncowati. The type of research used is descriptive qualitative. The techniques used in collecting data are complete participatory observation, interviews, documentation, and non-tests. The learning theory used is Bloom's theory. The research process was carried out for 10 days with 2 days of observation and 8 days of drill method application. The class teacher applies the lesson by presenting material about the history and function of the Sigeh Pengunten Dance. The class teacher prepares speakers and videos so that students can observe the movements of the Sigeh Pengunten Dance more clearly. In the process of applying the drill method, students prepare by warming up first. Students carry out the Sigeh Pengunten Dance range of motion exercises by following the directions of the class teacher and examples of the range of motions given by the researcher. The range of movements of the Sigeh Pengunten Dance is divided into 3 parts: the range of movements of part 1, the range of movements of part 2, and the range of movements of part 3. All parts of the range of movements have been sequential according to the composition of the Sigeh Pengunten Dance. In the learning process teachers and researchers are open to actively involving students to move following the examples of the range of motion given, openly react, and respond to the student's training process. At the last meeting, students were shown to be able to perform the Sigeh Pengunten Dance memorized and skilled which was witnessed by their colleagues and the school.